Hypnosis in psychotherapy, psychosomatics and medicine. A brief overview - Peter, Burkhard (Frontiers in Psychology, 2024)
Aspects of hypnosis and its application in psychotherapy, psychosomatics and medicine are examined and contextualized in the 250-year history of hypnosis. Imagination as an essential element of hypnotic treatments appeared as early as 1784 as an argument rejecting the theory of animal magnetism of Franz Anton Mesmer. In somnambulism of German romanticism, another proto-form of hypnosis after 1800, concepts of the mind–body problem were dealt with, which still characterize the understanding of unconscious mental processes today. Hypnosis was at the beginning of psychoanalysis, but was not pursued further by Sigmund Freud from 1900 onwards. Nevertheless, there were some hypnoanalytical approaches in the 20th century, as well as attempts to integrate hypnosis into behavior therapy. Techniques of imagination and relaxation combine both; in particular findings from cognitive psychology explain processes of both hypnosis and cognitive behavioral therapy. The influence of social psychology brought a new perspective to the debate about the nature of hypnosis, which continues to this day: is hypnosis to be understood as a special state of consciousness or is it a completely normal, mundane interaction? The experiments that were carried out to support one side or the other were also dependent on the hypnotizability of the subjects involved, as the more difficult hypnotic phenomena such as paralysis, hallucinations or identity delusions can only be demonstrated by highly hypnotizable subjects. The fact that these are not mere compliance reactions has now been proven by many studies using imaging techniques. But even those who are moderately hypnotizable benefit from hypnosis rituals. Variables postulated by socio-cognitive hypnosis researchers, such as motivation and expectation, are relevant, as is a good “hypnotic rapport.” Practical application of hypnotherapy today is characterized by the innovative techniques and strategies developed by Milton H. Erickson. Research into the effectiveness of hypnosis in the field of psychotherapy and psychosomatics still leaves much to be done. The situation is different in the field of medical hypnosis, where there are considerably more studies with a satisfactory design and verifiable effects. However, the impact in practical application in everyday medical practice is still low. Newer developments such as virtual reality and artificial intelligence are being looked at with critical interest.